Molecular characterization of indigenous microbes and its potential as a biological control agent of Fusarium stem rot disease (Fusarium verticillioides) on maize. Issue 12 (December 2022) - Mirsam, Hishar; Suriani,; Aqil, Muhammad; Azrai, Muhammad; Efendi, Roy; Muliadi, Ahmad; Sembiring, Hasil; Azis, Asti Irawanti
Abstract: Fusarium stem rot disease caused by Fusarium verticillioides has become one of the most serious issues confronting Indonesian farmers in recent years. An alternative option for suppressing this disease is to use indigenous microbes as an eco-friendly method to reduce synthetic fungicides. The objective of the research was to identify the molecular characteristics and effectiveness of an indigenous microbial consortium in controlling Fusarium stem rot disease. Identification of indigenous microbes is carried out based on molecular characters using universal primers, namely ITS-1/ITS-4 for fungi and 27F/1492R for bacteria. Nucleotide sequences were analyzed using Bioedit 7.2 version and MEGAX software. In vitro testing was carried out using the dual culture method for indigenous fungi and the disc diffusion method for indigenous bacteria. Meanwhile, in planta testing was conducted by evaluating a consortium of fungi and bacteria to control F. verticillioides in the field using a randomized block design with three replications, followed by a 5% DMRT test. The use of universal primer pairs ITS-1/ITS-4 and 27F/1492R succeeded in amplifying DNA bands of indigenous microbial isolates measuring ±600 bp and ±1465 bp, respectively. S6 and S9 bacterial isolates were identified as Bacillus cereus . JRP 7 and SEDF 6A isolates were identified as Trichoderma asperellum and JRP 10 isolate was identified as Penicillium raperi . All identification resulted in homology of >99%. The in vitro inhibitory reactions of isolates JRP 7, JRP 10, SEDF 6A, S6, and S9 against F. verticillioides were >60%. Disease severity of B6B9C10, B6B9C6, B6B9C7, B9C6C7, B9C7C10, and C6C7C10 treatments significantly proved their ability to control F. verticillioides in the field with a lower percentage of disease severity than positive controls, which are 23.33%, 18.89%, 23.33%., 21.85%, 14.07%, and 15.93%, respectively. The B9C7C10 consortium (S9 + JRP 7 + JRP 10 isolates) containing three species of indigenous microbes, i.e. B. cereus, T. asperellum, and P. raperi is the most effective at controlling F. verticillioides and may be developed for use as biopesticide products. Abstract : Antagonist; Bacteria; Consortium microbes; Fungi; Molecular.